Livecoderas Latinoamericanas : Diversity, educational access and musicking networks in live coding in Latin America. - Wilde, Emma; Duarte-García, Mario Alberto (Organised Sound, 2023)
Live coding in Latin America has always been tied to educational access concerns and has been disseminated through the region by way of free workshops offered outside of academic institutions. Although there is significant live coding activity in Latin America, live coding outside of the European context has been little explored. We interviewed 11 female practitioners active in live coding nodes in Latin America to uncover the challenges this group faces in terms of access to music education and live coding with the aim of determining what strategies can be implemented to mitigate these challenges and promote diversity in the future. We also consider the role of collective activity and how interaction between live coding nodes in the region has led to the formation of safe spaces in which participants can share resources. The results show that live coding offers attractions for those who have faced challenges in music academia while those with non-music backgrounds found an introduction to sound creation through live coding. This suggests that live coding provides new opportunities for inclusiveness that could be taken advantage of by music academics.